(untitled) (Studia austriaca, 2014)
Theodor Däubler spent a long period in Florence. His participation in the Futurist evenings is a recurrent theme in his letters to his friend Arthur Moeller van der Bruck, in which he also expresses his views on Marinetti, his admiration for the poet Italo Tavolato and for Aldo Palazzeschi (whose poems he later translated) and his recurring thoughts about Trieste. Däubler left Florence in 1914. His departure from Italy certainly represented a gradual (or maybe abrupt) detachment from this Futurist experience, a reality which he had lived and shared but never entirely embraced.